Development of an ELISA as a complement to MAT for swine leptospirosis diagnosis - Esteban, Micaela (2026)
Leptospirosis is a widespread zoonotic disease caused by pathogenic spirochetes of the genus Leptospira, affecting humans and a broad range of domestic and wild animals, which act as maintenance or incidental hosts. In swine, infection is associated with reproductive losses and significant economic impact. Transmission occurs through direct or indirect contact with contaminated urine, soil, or water. In small-scale and extensive production systems, frequent exposure to mud, stagnant water, and wildlife increases the risk of infection with multiple Leptospira serovars, complicating diagnosis. Rapid and reliable diagnostic tools are therefore essential for effective surveillance and control. The aim of this study was to evaluate an enzyme-linked immunosorbent assay (ELISA) based on a bacterial sonicated antigen as a complementary method to the microscopic agglutination test (MAT). Using MAT as the reference method, a panel of swine sera was analyzed to determine diagnostic performance. The ELISA showed a sensitivity of 83% and a specificity of 96%, demonstrating good agreement with MAT. These results indicate that the assay provides acceptable diagnostic accuracy and may serve as a practical complementary tool for herd-level screening and surveillance of swine leptospirosis.